Polyketide synthesis in tobacco plants transformed with a plumbago zeylanica type III hexaketide synthase - Jadhav, Supriya; Phapale, Prasad; Thulasiram, Hirekodathakallu V.; Bhargava, Sujata (Phytochemistry, 2014)
A type III polyketide synthase from Plumbago zeylanica (PzPKS) was cloned and expressed in tobacco plants to study whether the transgenic tobacco plants expressing PzPKS synthesize the pharmacologically important polyketide, plumbagin. High resolution mass spectrometry based metabolite profiling of two transgenic events and wild type tobacco plants was carried out to investigate changes in polyketides, including plumbagin. Ten polyketides, which included six pyrones and four naphthalene derivatives, were identified in PzPKS transgenic plants. While one pyrone, styry1-2-pyranone, was detected in both, wild type and transgenic tobacco plants, three pyrones were expressed only in the leaves of transgenic tobacco plants. The transgenic tobacco plants did not accumulate plumbagin, but showed accumulation of isoshinanolone in the roots, which is postulated to be the reduction product of plumbagin. In addition, leaves of transgenic tobacco plants accumulated 3-methyl-1,8-naphthalenediol, a postulated precursor of plumbagin. The results indicated the requirement of additional Plumbago-specific components in the biosynthetic pathway of this polyketide. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: HR-MS; Metabolite profiling; Napthalene derivatives; Plumbago zeylanica L.; Polyketide synthase; Pyrones; Tobacco transgenics

Role of methyl jasmonate in the expression of mycorrhizal induced resistance against Fusarium oxysporum in tomato plants - Nair, Aswathy; Kolet, Swati P.; Thulasiram, Hirekodathakallu V.; Bhargava, Sujata (Physiological and Molecular Plant Pathology, 2015)
Arbuscular mycorrhiza (AM) colonization led to a decrease in the severity of fusarium wilt disease caused by Fusarium oxysporum f. sp. lycopersici in tomato plants. The involvement of two plant defense hormones, namely methyl jasmonate (MeJA) and salicylic acid (SA), in the expression of mycorrhiza induced resistance (MIR) against this vascular pathogen was studied in the AM colonized and non-colonized (controls) plants. Activity of lipoxygenase (LOX), which plays a role in jasmonic acid (JA) biosynthesis, as well as levels of methyl jasmonate (MeJA) increased in AM colonized plants as compared to controls, but did not show any further changes in response to F. oxysporum inoculation. On the other hand, activity of phenylalanine ammonia lyase (PAL), which is an enzyme from salicylic acid (SA) biosynthetic pathway, as well as SA levels, increased in both controls and AM colonized plants in response to application of F. oxysporum spores. Hence the JA and not the SA signalling pathway appeared to play a role in the expression of MIR against this vascular pathogen. The resistance observed in AM colonized plants was completely compromised when plants were treated with the JA biosynthesis inhibitor salicylhydroxamic acid (SHAM). This confirmed that the AM-induced increase in JA levels was involved in the expression of resistance toward F. oxysporum. The SA response gene pathogenesis-related 1 (PR1) showed an increased expression in response to F. oxysporum infection in SHAM treated AM colonized plants as compared to plants that were not treated with this JA inhibitor. This suggested the possibility that JA inhibited SA responses, at least in the roots. AM colonization therefore appeared to prime plants for improved tolerance against the vascular pathogen F. oxysporum, which was mediated through the JA signalling pathway. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Fusarium wilt; Glomus fasciculatum; Methyl jasmonate; Mycorrhiza induced resistance; Salicylic acid; Tomato

Role of jasmonate in modulation of mycorrhizae-induced resistance against fungal pathogens - Nair, Aswathy; Thulasiram, H. V.; Bhargava, Sujata (Methods in Molecular Biology, 2020)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Symbiotic association of plants with arbuscular mycorrhizal (AM) fungi brings about changes in levels of the phytohormone jasmonate (JA) in root and shoot tissues of a plant. The enhanced JA levels not only play a role in controlling the extent of AM colonization but are also involved in the expression of mycorrhizal-induced resistance (MIR) against pathogens. We describe a method used to study the levels of a volatile jasmonate derivative, methyl jasmonate (MeJA), in tomato plants colonized by AM fungi and in response to subsequent attack by the foliar pathogen Alternaria alternata.